2017
DOI: 10.1021/acs.chemmater.7b04925
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Colloidal Copper Indium Sulfide Nanosheets by Two-Dimensional Self-Organization

Abstract: Colloidal 2D semiconductor nanosheets (NSs) are an interesting new class of materials due to their unique properties. However, synthesis of these NSs is challenging, and synthesis procedures for materials other than the well-known Pb- and Cd-chalcogenides are still underdeveloped. In this paper, we present a new approach to make copper indium sulfide (CIS) NSs and study their structural and optical properties. The CIS NSs form via self-organization and oriented attachment of 2.5 nm chalcopyrite CuInS2 nanocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…This process converts the CIS seed NCs into In-poor CIS NCs, which subsequently undergo 2D self-organization and oriented attachment, yielding In-poor CIS nanosheets. 43 This demonstrates that S-ODE/OLAM is capable of quickly extracting In 3+ (and to a lesser extent Cu + ) from CIS NCs, thereby leading to pronounced etching, which is characterized by large blue-shifts accompanied by large reductions in the In/Cu ratio and low Zn-content. The extent of the etching is directly related to the reactivity of the Zn-precursor: an unreactive Zn-precursor, such as ZnSt 2 , is unable to react with the S-precursors fast enough to outcompete the In-extraction reaction, thereby resulting in pronounced etching, followed by 2D self-organization.…”
Section: Resultsmentioning
confidence: 88%
“…This process converts the CIS seed NCs into In-poor CIS NCs, which subsequently undergo 2D self-organization and oriented attachment, yielding In-poor CIS nanosheets. 43 This demonstrates that S-ODE/OLAM is capable of quickly extracting In 3+ (and to a lesser extent Cu + ) from CIS NCs, thereby leading to pronounced etching, which is characterized by large blue-shifts accompanied by large reductions in the In/Cu ratio and low Zn-content. The extent of the etching is directly related to the reactivity of the Zn-precursor: an unreactive Zn-precursor, such as ZnSt 2 , is unable to react with the S-precursors fast enough to outcompete the In-extraction reaction, thereby resulting in pronounced etching, followed by 2D self-organization.…”
Section: Resultsmentioning
confidence: 88%
“…The strong and broad NIR absorption bands observed in the spectra of the product CIS/ZnS HNCs obtained by using injection methods II and III ( Figure S3 ) are assigned to localized surface plasmon resonances (LSPR), which are often observed in Cu-chalcogenide NCs. 9 , 24 , 25 LSPR bands involve excess charge carriers, which are due to stoichiometry deviations, typically Cu-vacancies, which lead to excess holes in the valence band. 9 , 24 However, LSPRs due to In-vacancies have also been reported.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 9 , 24 However, LSPRs due to In-vacancies have also been reported. 25 These observations imply that methods II and III lead to product HNCs that are rich in cation (Cu or In) vacancies, in contrast to method IV.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ligands in stabilizing facets is a well-known phenomenon. 19 For example, it has been shown that alkylamines stabilize the high energy (001) top and bottom facets of covellite CIS nanosheets, 52 oleic acid directs the 2D-growth of PbS by stabilizing the (100) facet, 53 and amines and DDT stabilize different djurleite Cu 2– x S facets, thereby providing control over where CE reactions take place and consequently over the morphology of Cu 2– x S/I–III–VI 2 hetero-nanorods. 54 We thus conclude that the driving force for the internal reconstruction process that accompanies the structural transformation of the nanoplatelets from tetragonal umangite Cu 2– x Se to hexagonal wurtzite CdSe and CuInSe 2 is likely the minimization of both the total surface free energy and the reconstruction strain during the structural reorganization process, in such a way that the total volume expansion work is kept to a minimum ( V Cu 2 Se = 1.7 × 10 3 nm 3 , V CdSe = 2.1 × 10 3 nm 3 , V CuInSe 2 = 1.8 × 10 3 nm 3 ).…”
Section: Resultsmentioning
confidence: 99%